Sandy Jacobs-Tolle COVID-19 Social Media Post Petting Cat's Head with Knit Glove - Jacobs-Tolle, Sandy:::::::::
One in a series of six social media posts showing Sandy Jacobs-Tolle's COVID-19 knitting projects.